Value in 3-D: new Windows operating systems and powerful programming tools are converging to create new price/performance point in solid-modeling, mechanical design software.(IW Electronics and Technology: Tech Focus) - Stevens, Tim (Industry week, 1996)
Three-dimensional solid modeling software is emerging on the market that is both low-cost and compliant with the Windows NT and Windows 95 environments. Although programs such as Solid Works 95 and Solid Edge are not designed to replace high-end modeling programs, they will appeal to many 2-D CAD users who want to upgrade.